PD‐L1 and LAG‐3 expression in advanced cutaneous squamous cell carcinomas. (11th June 2020) - Wu, Sam; Slater, Nathaniel A.; Sayed, Christopher J.; Googe, Paul B.
Abstract: Background: Expression of programmed death ligand 1 (PD‐L1) by cutaneous squamous cell carcinomas has been shown to correlate with advanced disease and risk of metastasis. Lymphocyte activation gene 3 (LAG‐3, or CD223) is an inhibitory receptor that interacts with the PD‐L1 axis, which has been shown to be a marker of immune exhaustion and a potential immunotherapy target. However, the role of LAG‐3 in cutaneous squamous cell carcinoma has not been established. Methods: We reviewed 18 cases of locally advanced and/or metastatic cutaneous squamous cell carcinomas and assessed for PD‐L1 expression, presence or absence of tumor‐infiltrating lymphocytes (TILs), and expression of LAG‐3 by TILs. Results: PD‐L1 expression was present in 11 of 13 locally advanced primary tumors and 5 of 5 metastases. TILs were present in all 18 tumors, of which 14 cases were positive for LAG‐3 expression. In positive cases, LAG‐3 was expressed on average by 32% of TILs. Conclusions: Advanced cutaneous squamous cell carcinomas frequently express PD‐L1 and are associated with an inflammatory response. LAG‐3 expression by TILs was identified in a majority of cases. Our findings suggest that LAG‐3 positive tumor‐associated inflammatory cells may play a role in the development of advanced disease and offer another potential target for drug therapy.